THE RELATIONSHIP OF PHUBBING, EMOTIONAL INTELLIGENCE AND PSYCHOLOGICAL DISTRESS IN YOUTH - Sana Arshad; Ayesha Sarwar; Ayub, Sumaira; Nimra Qamar (Journal of Pakistan Psychiatric Society, 2024)
Objectives: The purpose of this study was to investigate the relationship between phubbing behavior, emotional intelligence, and psychological distress in youth and the predicting role of phubbing and emotional intelligence in determining psychological distress in youth. Research Design: Correlational research design was used. Place And Duration of Study: This study was conducted between March 2022 to February 2023 at Department of Applied Psychology, University of Management and Technology Lahore. Subjects and Methods: A total of 200 university students aged between 18 and 26 (M =21.36; SD =1.94) were selected from different public and private sector universities of Lahore through convenient sampling technique. The Phubbing Scale,54 Wong and Law Emotional Intelligence Scale,55 and Depression, Anxiety and Stress Scale 2156 along with self-constructed demographic sheet were used to collect data. Results: The results revealed a positive relationship between phubbing and psychological distress in young adults. Further, phubbing was found to be a significant predictor of psychological distress in young adults, however Overall emotional intelligence did not predict it. Further, no significant gender differences were found in phubbing, emotional intelligence, and psychological distress. Conclusion: The study highlights the impact of excessive mobile usage on emotional intelligence and psychological distress levels and may help in proposing interventions to reduce phubbing and improve emotional intelligence as potential solutions to mitigate psychological distress.